2020
DOI: 10.3390/ma13204673
|View full text |Cite
|
Sign up to set email alerts
|

Surface Activation of Polylactic Acid-Based Wood-Plastic Composite by Atmospheric Pressure Plasma Treatment

Abstract: Wood-plastic composite (WPC) based on a polylactic acid (PLA) matrix is a promising material since it is biobased, degradable, sustainable, and 3D printable. However, due to its coloring, visible layers after 3D-printing, and small build volumes of these printers, a coating or gluing of parts might be required. This study investigates the influence of a dielectric barrier discharge (DBD) plasma treatment of PLA-based WPC to activate the surface and improve, e.g., coating capabilities. X-ray photoelectron spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…The effect of increasing surface hydrophilicity with plasma treatment is well known and expected. Sauerbier and co-authors [ 11 ] reported that water contact angles on a PLA-based wood-polymer composite (WPC) with 60% wood content decreased significantly after plasma treatment. A similar effect of plasmas is reported on ABS [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of increasing surface hydrophilicity with plasma treatment is well known and expected. Sauerbier and co-authors [ 11 ] reported that water contact angles on a PLA-based wood-polymer composite (WPC) with 60% wood content decreased significantly after plasma treatment. A similar effect of plasmas is reported on ABS [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Proper surface adhesion is required for bonding and coating processes. The coating of AM produced parts is often necessary since the AM process leaves behind individual visual and haptic layers that have to be sanded, filled, sanded again and finally painted [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations